Comparative Analysis Of The Number Word Class (On The Example Of Uzbek, Russian And English Languages) - Uktamova, Mokhigul; Abobakirova, Shahrizoda (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article is aimed at analyzing the role of the number word class in Uzbek linguistics, its lexical-semantic features and grammatical nature. The study covers the types of meanings of numbers, their formation system and the laws of their connection with other word classes, in particular nouns, in a sentence. Also, the stylistic features of the use of numbers in speech and with numeral words are analyzed using examples.